Ethics of Care
DOI: 10.2307/j.ctt1t89d95.16
|View full text |Cite
|
Sign up to set email alerts
|

HIV care and interdependence in Tanzania and Uganda

Abstract: Within many communities in East Africa, people living with HIV are increasingly involved in delivering home-based care and healthcare for family members and peers. Such interdependent caring relations blur conventional boundaries between 'care-givers' and 'carerecipients', and constructions of 'service users' as dependent, passive recipients of healthcare. The participation of people living with HIV in healthcare provision, home-based care and peer support groups can enhance 'relational autonomy' for both care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Research that does consider relatives’ perspectives, draws on an ethics of care framework to make visible the caring practices and interactions that are mobilised within family structures. These studies have identified HIV care interdependencies in African settings (Evans & Atim, 2015; Skovdal et al., 2018), with some noting how conflicting emotional connections between care providers and receivers may constrain “good care” (Evans & Thomas, 2009), and shape the availability of resources to provide and receive care, particularly in contexts of stigma, and social and economic inequality. We contribute to the expansion of the ethics of care framework in HIV care, exploring the perspectives of next-of-kin who have lost a relative to AIDS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research that does consider relatives’ perspectives, draws on an ethics of care framework to make visible the caring practices and interactions that are mobilised within family structures. These studies have identified HIV care interdependencies in African settings (Evans & Atim, 2015; Skovdal et al., 2018), with some noting how conflicting emotional connections between care providers and receivers may constrain “good care” (Evans & Thomas, 2009), and shape the availability of resources to provide and receive care, particularly in contexts of stigma, and social and economic inequality. We contribute to the expansion of the ethics of care framework in HIV care, exploring the perspectives of next-of-kin who have lost a relative to AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…Being able to react, adjust and advance their care, based on these reactions and responses requires the responsiveness of the relative for caregiving to continue. This framework allows an exploration of the influences on the evolution of the care relationships that existed between the caregivers and their recently deceased relatives, and has proved to be particularly useful in disentangling the morality and dynamics of care in the contexts of HIV and stigma (Evans & Atim, 2015; Evans & Thomas, 2009). More recently, Tronto (2013) has proposed a fifth phase of care, namely “caring with”, referring to the politics of availing care support in ways that uphold democratic commitments to justice, equality and freedom for all.…”
Section: Introductionmentioning
confidence: 99%